Effects of concurrent training on explosive strength and VO2max in prepubescent children - Marta, C.; Marinho, D. A.; Barbosa, T. M.; Izquierdo, M.; Marques, M. C. (International Journal of Sports Medicine, 2013)
The purpose of this study was to compare the effects of an 8-weeks training period of resistance training alone (GR), combined resistance and endurance training (GCON) and a control group (GC) on explosive strength and VO2max in a large sample of prepubescent boys and girls. 125 healthy children (58 boys, 67 girls), aged 10-11 years old (10.8±0.4 years) were assigned into 2 training groups to train twice a week for 8 weeks: GR (19 boys, 22 girls), GCON (21 boys, 24 girls) and a control group (GC: 18 boys, 21 girls; no training program). A significant but medium-sized increase from pre- to the post-training in the vertical jump (Effect size=0.22, F=34.44, p<0.01) and VO2max (Effect size=0.19, F=32.89, p<0.01) was observed. A significant large increase in the 1 kg (Effect size=0.53, F=202.17, p<0.01) and 3 kg (Effect size=0.48, F=132.1, p<0.01) ball throwing, standing long jump (Effect size=0.53, F=72.93, p<0.01) and running speed (Effect size=0.45, F=122.21, p<0.01) was also observed. The training group (GR and GCON) and sex factors did not significantly influence the evolution of strength variables from pre- to the post-training. The VO2max increased significantly only in GCON. Concurrent training is equally effective on training-induced explosive strength, and more efficient than resistance training only for VO2max, in prepubescent boys and girls. This should be taken into consideration in order to optimize strength training school-based programs.